Development prospects for Bazhenov formation bituminous claystones in the southeast of the West Siberian Plate (Tomsk Region); IOP Conference Series: Earth and Environmental Science; Vol. 24 : Scientific and Technical Challenges in the Well Drilling Progress, 24–27 November 2014, Tomsk, Russia - Belozerov V. B. Vladimir Borisovich (2015, 2015)
Title screen